Which equation is equivalent to 4x + 3 + (-3x) + 7x - 6x = 11?

A.
8x + 3 = 11

B.
2x + 3 = 11

C.
5x = 11

D.
-4x = 11

1 answer

Let's simplify the left side of the equation step by step:

Given the equation: \[ 4x + 3 + (-3x) + 7x - 6x = 11 \]

First, combine the terms involving \( x \):

  • \( 4x - 3x + 7x - 6x \)

Now, calculate each step:

  1. \( 4x - 3x = 1x \)
  2. Adding \( 7x \) gives \( 1x + 7x = 8x \)
  3. Subtracting \( 6x \) gives \( 8x - 6x = 2x \)

Thus, we have: \[ 2x + 3 = 11 \]

Now, comparing with the options provided, we see that: B. \( 2x + 3 = 11 \) is the correct equivalent equation.

Similar Questions
  1. 1. which equation is equivalent to y - 6 = -12(x+4)?2. which point is located on the line represented by the equation y + 4 =
    1. answers icon 80 answers
    1. answers icon 2 answers
    1. answers icon 6 answers
  2. 1.what equation is equivalent to y-6=-12(x+4)2. which point is located on the line represented by the equation y+4=-5(x-3)?
    1. answers icon 17 answers
more similar questions